DIFFERENCES OF TESTOSTERONE LEVELS TO THE DURATION OF INHALED NICOTINE EXPOSURE IN SPRAGUE-DAWLEY MALE WHITE RATS - Ramadhan, Ido Putra; Djojodimedjo, Tarmono; Soebadi, Doddy M (Indonesian Journal of Urology, 2020)
Objective: To analyze the differences in testosterone level in young Sprague-Dawley white rats after exposure of inhaled nicotine and the recovery effect that occurs when nicotine exposure is stopped. Material & Methods: This is an experimental study, which variable measurements were taken after the experimental animals were treated. The experimental grouping process was carried out randomly, with repetitions of 12 experimental animals in each group and the control group as a comparison (negative control). This study using male Sprague-Dawley white rats as samples. Nicotine administration was carried out by inhalation using pure nicotine (C10H14N2), which was diluted using distilled water. Treatment group 1 (P1) was given nicotine exposure for 30 days, treatment group 2 (P2) for 15 days, and treatment group 3 (P3) for 15 days and then stopped for 15 days compared to the control group. Testosterone levels are measured using the ELISA (Enzyme-Linked Immunosorbent Assay) method in the morning. Results: The lowest testosterone levels were found in the P1 and significantly different from the P2 (p=0.029) and P3 (p=0.001). The results of the analysis show that a decrease in testosterone levels in mice is related to the duration of nicotine exposure. Conclusion: Testosterone levels in the control group were significantly higher compared to the treatment group that exposed by nicotine inhalation with a dose of 4 mg/kgBW/day for 15 days, and also there is a significant recovery effect on testosterone levels after the treatment was halted for 15 days.